Novel experience induces persistent sleep-dependent plasticity in the cortex but not in the hippocampus - Ribeiro, Sidarta; Shi, Xinwu; Engelhard, Matthew; Zhou, Yi; Zhang, Hao; Gervasoni, Damien; Lin, Shih-Chieh; Wada, Kazuhiro; Lemos, Nelson A.; Nicolelis, Miguel A. (Frontiers in Neuroscience, 2007)
Episodic and spatial memories engage the hippocampus during acquisition but migrate to the cerebral cortex over time. We have recently proposed that the interplay between slow-wave (SWS) and rapid eye movement (REM) sleep propagates recent synaptic changes from the hippocampus to the cortex. To test this theory, we jointly assessed extracellular neuronal activity, local field potentials (LFP), and expression levels of plasticity-related immediate-early genes (IEG) arc and zif-268 in rats exposed to novel spatio-tactile experience. Post-experience firing rate increases were strongest in SWS and lasted much longer in the cortex (hours) than in the hippocampus (minutes). During REM sleep, firing rates showed strong temporal dependence across brain areas: cortical activation during experience predicted hippocampal activity in the first post-experience hour, while hippocampal activation during experience predicted cortical activity in the third post-experience hour. Four hours after experience, IEG expression was specifically upregulated during REM sleep in the cortex, but not in the hippocampus. Arc gene expression in the cortex was proportional to LFP amplitude in the spindle-range (10-14 Hz) but not to firing rates, as expected from signals more related to dendritic input than to somatic output. The results indicate that hippocampo-cortical activation during waking is followed by multiple waves of cortical plasticity as full sleep cycles recur. The absence of equivalent changes in the hippocampus may explain its mnemonic disengagement over time.